Severe Hail Storm at Thori: A Case Study - Aryal, Deepak (Tribhuvan University Journal, 2018)
During the pre-monsoon months (March-May) in Nepal, severe thunder and hailstorms cause significant property and agricultural damage in addition to loss of life from lightening. Forecasting thunderstorm severity remains a challenge even in wealthy, developed countries that have modern meteorological data gathering infrastructure, such as Doppler Radar. This study attempts to isolate the specific and unique characteristics of a hailstorm that not only might explain its severity, but also suggest forecasting techniquees for future forecasting in Nepal. The primary data sources for this investigation included Infrared Satellite images, which illustrated the sequences of convective activity, and original archived ESRLIndia and China upper air data, which was used for synoptic and mesoscale analyses. On May 3, 2001 between the hours of 1100pm and midnight, a severe thunderstorm accompanied by hail stones estimated at 1kg, devastated the village of Thori (Southern border to India). 800 thatched houses were destroyed, over 500 farm animals were killed and more than 200 hectares of crops lost. Many inhabitants were injured, but luckily only one death. Thori hail storm had its origins in a topographically induced lee-side convergence area in the deserts of Pakistan on May 2, 2001, from where it propagated eastwards into India and evolved into an eastward travelling Mesoscale Convective System reaching Thori near midnight on May 3. Atmospheric instability over the Gangetic Plains, fuelled by a very active surface heat low, cold temperatures and dynamic lifting mechanisms aloft, created a synoptic and mesoscale environment capable of generating a dangerous thunderstorm.